THE INFLUENCE AND SIGNIFICANCE OF INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF A PERSON ON THE SOCIAL ENVIRONMENT - Toshpulatov Ibrohim Ikromjonovich; Muxammadjanova Muhlisa Abdulla qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article discusses the individual psychological characteristics of a person and their impact on human activity, communication, and the social environment. The psychological characteristics of a person play a wide role, from his decision-making process to his success in social life. The article uses psychological theories, psychological analysis methods, and experimental approaches to analyze the characteristics of a person. It also discusses various personal characteristics (for example, introversion and extraversion, emotional stability, social sensitivity, etc.) and their impact on a person's role and relationships in society. This study helps to understand the individual psychological characteristics of a person more deeply and serves to develop the necessary skills for effective communication in interpersonal relationships.